ОЦІНКА ШВИДКОСТІ СТАРІННЯ ПОЛІМЕРНОЇ ІЗОЛЯЦІЇ СИЛОВОГО КАБЕЛЮ ПІД ДІЄЮ ПЕРИОДИЧНОЇ НЕСИНУСОЇДНОЇ НАПРУГИ - Подольцев, O.Д.; Ломко, М.О. (Інститут електродинаміки НАН України, Київ, 2023)
The paper proposes a method for estimating the rate of water treeing growth in the polymer insulation of the power cable, taking into account the presence of higher voltage harmonics. The technique allows to predict the service life of a cable used in a power grid with a distorted voltage, depending on the frequency spectrum of this voltage, as well as to select at the design stage of the cable line the calculated value of the nominal voltage of the cable the service life of the cable will be the same as when operating normally. To implement this technique, a computer program in the Matlab/Simulink package has been developed, which allows to perform appropriate calculations and estimate the service life of the cable insulation according to a predetermined form of distorted voltage in the power grid. For the voltage oscillogram considered as an example, characterized by the value of THDU = 23.4%, it is shown that the value of the relative water treeing growth is equal 1.62, and the service life of the cable will be 0.62 of its service life when operating normally. References 6, figures 4.